Лiнiйна та нелiнiйно-оптична характеризацiя гiбридiв на основi TiO2 при самовпливi неперервного лазерного випромiнювання та пiкосекундних лазерних iмпульсiв - Uklein, A. V.; Multian, V. V.; Gayvoronsky, V. Ya. (Publishing house "Academperiodika", 2018)
The impact of the concentration of TiO2 nanoparticles on the optical and nonlinear optical (NLO) response of TiO2-based hybrids is studied. The characterization of variations of the optical scattering, photoinduced absorption, and refractive index under the excitation of continuous (CW) and picosecond laser pulses of studied samples is performed. The manifestation of the cooperative eﬀect of nanoparticles at concentrations higher 4.4 ×1020 cm−3 of Ti atoms is observed. The eﬀect is accompanied with the enhancement of the eﬃciency of charge separation processes at the organic-inorganic interface and with the photoinduced Ti^3+ centers polarizability reduction. The observed results indicate the optimal titanium concentration about 4.4 ×1020 cm−3 for the photonics application.